Interchange Fees as a Mechanism to Raise Rivals' Costs - Some Evidence from Switzerland - Samuel Rutz (Swiss Journal of Economics and Statistics, 2010)
In 2004 the Swiss Competition Commission (ComCo) opened an investigation concerning multilateral agreed interchange fees in the Swiss credit card market which ended with an amicable settlement. The most important element of this amicable settlement consists in the limitation of the interchange fee to the actual network costs of the issuers. In this paper I discuss whether there was a market failure in the Swiss credit card market which justified the intervention by ComCo and whether the remedies imposed in the amicable settlement eliminated the alleged market failure.
Keywords: L4; G2; 330; antitrust; payment systems; interchange fees; two-sided markets